Ultrasound in early pregnancy by village midwives in Sudan - E.Maruod, Maruod; Yusuf, Dr.Alsawi YA; Awadalla, Dr.Khidir E (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Antenatal care services are provided by village midwives in rural communities in Sudan .Village midwives are well trained in the detection of pregnancy complications in late pregnancy. Early pregnancy problems constitute a real challenge because they require special skills of pelvic examinationand imaging techniques. Ultrasound is an essential and safe tool in managing pregnancy in modern obstetric practice. However, in low-resource countries, the technique is not widely available. Due to the high pregnancy-associated morbidity and mortality in these settings it may be justifiable to provide village midwives with US technology. The aim of this pilot study was to systematically train village midwives to use ultrasound in the evaluation of early pregnancy in Damira district, a rural community in NorthKordofanState, Western Sudan.